Efektivitas Penggunaan Media Interaktif Quizizz Terhadap Hasil Belajar Siswa SMK Negeri 2 Tebo - Bowo Santoso, Jarot Tri; Prabawati, Arrum; Octavianto, Said Nur (Universitas Negeri Semarang, 2023)
The purpose of this study was to analyze the effectiveness of using interactive learning media quizizz on learning outcomes of Accounting as an Information System in class XI Accounting at SMK Negeri 2 Tebo in the 2022/2023 learning year. This experimental research was conducted at SMK Negeri 2 Tebo. The experimental class was selected XI Accounting 1 class and XI Accounting II control class because the two classes had almost the same average daily score. Data was taken with tests, namely pre tests and post tests in both classes. The data were analyzed by Paired Sample T Test and Independent t test. The results showed that (1) Quizizz Interactive Media was able to improve student learning outcomes, (2) Quizizz Interactive Media was effective in improving student learning outcomes.